The process of hypertension induced by high-salt diet: Association with interactions between intestinal mucosal microbiota, and chronic low-grade inflammation, end-organ damage - Zheng, Tao; Wu, Yi; Guo, Kang-xiao; Tan, Zhou-jin; Yang, Tao (Frontiers in Microbiology, 2023)
Inflammation and immunity play a major role in the development of hypertension, and a potential correlation between host mucosal immunity and inflammatory response regulation. We explored the changes of intestinal mucosal microbiota in hypertensive rats induced by high-salt diet and the potential link between the intestinal mucosal microbiota and inflammation in rats. Therefore, we used PacBio (Pacific Bioscience) SMRT sequencing technology to determine the structure of intestinal mucosal microbiota, used enzyme-linked immunosorbent assay (ELISA) to determined the proinflammatory cytokines and hormones associated with hypertension in serum, and used histopathology methods to observe the kidney and vascular structure. We performed a potential association analysis between intestinal mucosal characteristic bacteria and significantly different blood cytokines in hypertensive rats induced by high-salt. The results showed that the kidney and vascular structures of hypertensive rats induced by high salt were damaged, the serum concentration of necrosis factor-α (TNF-α), angiotensin II (AngII), interleukin-6 (IL-6), and interleukin-8 (IL-8) were significantly increased (p < 0.05), and the coefficient of immune organ spleen was significantly changed (p < 0.05), but there was no significant change in serum lipids (p > 0.05). From the perspective of gut microbiota, high-salt diet leads to significant changes in intestinal mucosal microbiota. Bifidobacterium animalis subsp. and Brachybacterium paraconglomeratum were the dominant differential bacteria in intestinal mucosal, with the AUC (area under curve) value of Bifidobacterium animalis subsp. and Brachybacterium paraconglomeratum were 1 and 0.875 according to ROC (receiver operating characteristic) analysis. Correlation analysis showed that Bifidobacterium animalis subsp. was correlated with IL-6, IL-8, TNF-α, and Ang II. Based on our results, we can speculated that high salt diet mediated chronic low-grade inflammation through inhibited the growth of Bifidobacterium animalis subsp. in intestinal mucosa and caused end-organ damage, which leads to hypertension.